Modern views on the role of main components of stroma and tumor microinvironment in invasion, migration and metastasis - Naleskina, L.A.; Kunska, L.M.; Chekhun, V.F. (PH Akademperiodyka, 2023)
Summary. The review presents modern ideas about tumor microenvironment, which most researchers recognize as the main “player” in tumor cell invasion, cell migration and metastasis. The current data on the main components of the stroma and the microenvironment, which play the role of the driving force in tumor progression, are analyzed. In particular, the review highlights the issues of origin, biological traits, phenotypic plasticity, functional heterogeneity of activated fibroblasts — myofibroblasts and tumor-associated fibroblasts, which in recent years have received much attention. Such components of the extracellular matrix proteome as collagen and matrix metalloproteinases are discussed in detail. They are mostly produced by activated fibroblasts and, on the one hand, initiate the development of desmoplasia due to type I collagen and, on the other hand, promote degradation of extracellular matrix proteins due to metalloproteinases, which generally leads to tissue remodeling that promotes tumor progression. Possibilities of using the most important indicators of extracellular matrix remodeling as potential markers and targets of clinical strategy are discussed.